Type 2 diabetes increases oocyte mtDNA mutations which are eliminated in the offspring by bottleneck effect - Li Li; Chang-Sheng Wu; Guan-Mei Hou; Ming-Zhe Dong; Zhen-Bo Wang; Yi Hou; Heide Schatten; Gui-Rong Zhang; Qing-Yuan Sun (Reproductive Biology and Endocrinology, 2018)
Abstract Background Diabetes induces many complications including reduced fertility and low oocyte quality, but whether it causes increased mtDNA mutations is unknown. Methods We generated a T2D mouse model by using high-fat-diet (HFD) and Streptozotocin (STZ) injection. We examined mtDNA mutations in oocytes of diabetic mice by high-throughput sequencing techniques. Results T2D mice showed glucose intolerance, insulin resistance, low fecundity compared to the control group. T2D oocytes showed increased mtDNA mutation sites and mutation numbers compared to the control counterparts. mtDNA mutation examination in F1 mice showed that the mitochondrial bottleneck could eliminate mtDNA mutations. Conclusions T2D mice have increased mtDNA mutation sites and mtDNA mutation numbers in oocytes compared to the counterparts, while these adverse effects can be eliminated by the bottleneck effect in their offspring. This is the first study using a small number of oocytes to examine mtDNA mutations in diabetic mothers and offspring.